Proceedings of the international conference on infrastructure renovation and waste control 8th-10th April 1986 : an international conference and exhibition to celebrate the North Western Association centenary - Proctor, D. C.; Whyte, I. L. (Manstock, 1986)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of ICE North West Association centenary conference held at UMIST on 8-10 April 1986.